Antifungal activity of plant extracts used in folk medicine in Argentina - Davicino, Roberto (2007)
Fungi may cause very serious diseases in humans specially in immunosuppressed patients. In this study, extracts of 10 plants used in popular medicine in Argentine were assayed for in vitro antifungal activity against 4 fungal strains. Out of all the plants tested, Larrea divaricata Cav, Gnaphalium gaudichaudianum D.C, Baccharis trimera Less and Schinus terebenthifolius proved to have antifungal activity.